Validation of a generic job satisfaction scale among libyan arabs: Exploring its association with mental health outcomes - Mohamed Ali; Marwa Dafous (Elsevier, 2024)
Background: The purpose of this research was to test psychometric proprieties of Macdonald & MacIntyre's Generic Job Satisfaction Scale (GJSS) between Arab workers. Method: The study involved 171 participants (average age = 39.2 years; standard deviation = 9.76) from Libyan Territory, with 45 % being male. Using a cross-sectional design, the study employed the translated GJSS Questionnaire, the Conditions for Workplace Effectiveness Questionnaire-II (CWEQ-II), and the Depression Anxiety Stress Scale 8-items (DASS-8). Results: Confirmatory Factor Analysis confirmed a one-dimensional structure with a satisfactory fit. The scale showed positive correlations, indicating adequate convergent validity with CWEQ-II dimensions such as Opportunity, Support, Resources, Formal Power (Job activity), and Structural Empowerment, as well as negative correlations suggestive of discriminant validity with the DASS-8 dimensions. Reliability indices, α = 0.87 and ω = 0.88, suggest satisfactory internal consistency and composite reliability of the instrument. Notably, women exhibited higher scores in the Job Satisfaction scale, Opportunity, Support, Formal Power (Job activity scale), and Structural Empowerment dimensions of the Workplace Effectiveness scale. Conclusion: the adapted scale GJSS exhibits reliability and validity, rendering it suitable for use among Arab populations.